جريمة الإرهاب الدولي وفقا للأحكام اتفاقية منظمة المؤتمر الإسلامي لعام 1999 - جامع شادي (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تعد ظاهرة الإرهاب الدولي من الظواهر الخطيرة في المجتمع الدولي و التي يمكن ان تستخدم لأغراض سياسية و بهدف الضغط على الدول و لهذه الظاهرة أهمية خاصة في منطقة الشرق الأوسط في ظل نزاعات حادة, لذلك أدرك المجتمع الدولي أهمية مسألة الإرهاب و قام بتبني عدة معاهدات دولية تحت اشرف الأمم المتحدة و المنظمات الإقليمية و العقائدية (كمنظمة المؤتمر الإسلامي), سنحاول في بحثنا إظهار مدى استقلالية الدين الإسلامي عن ظاهرة الإرهاب و إنكار التهمة الظالمة بان الإرهاب هو حالة مرتبطه بالدين الإسلامي سنتناول في بحثنا دراسة ظاهرة الإرهاب وفق معاهدة منظمة المؤتمر الإسلامي فسنعرض تعريف جريمة الإرهاب و أركانها و العقوبة المتوجبة عليها مع ربط هذا الموضوع بحالة الإرهاب التي تعاني منها سورية و التي تمارسه جماعات تكفيرية مستترة بأفكار دين متطرفة لا صلة لها بالدين الإسلامي. International terrorism is considered a serious problem in the international community which can be used for political purposes and to put pressure on countries. In the Middle East in particular, and in the light of sharp conflicts, the international community gave this issue special attention and adopted several treaties and agreements under the supervision of UN and other regional and religious organizations, such as the Organization of Islamic Conference. The study aims at presenting the discrepancy between Islam and terrorism in addition to challenging and denying the unfair charge that terrorism is linked to Islam. We will discuss in our study the phenomenon of terrorism in accordance with the Organization of the Islamic Conference Treaty and show the definition of the crime of terrorism and its cornerstones and penalty owed by linking this topic to the terrorism experienced by Syria and practiced by terrorist groups disguised by takfiri extremist ideas which are definitely unrelated to Islam.